Developing Global Human Resource Strategies - Hans-Erich Mueller (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
A few years ago it was typical to give one's subsidiaries a free rein and send managers overseas from headquarters only. But today a great deal depends on overcoming this one-way street and in looking for and employing the best-suited managers, regardless of their origins. What contribution can human resource management make towards a company's global orientation – an area in which local scope and latitude are traditionally very high? Our study shows that in recent years large US and German industrial enterprises have re-aligned the management of their executive staff. Cornerstones of this quiet revolution are a policy of worldwide parity of executives in evaluation, remuneration and development, greater participation of those with line responsibility from product areas and regions in strategic development, as well as a re-alignment of human resource instruments. Worldwide standards in human resource policy are key factors in the competition for qualified managers. Not only companies, but also executives need to adjust. How have these companies managed to press ahead this quantum leap in their international strategy for executives? What significance do local or cultural differences have, if any? What are the possible consequences of this job market opening? The following article makes “best practice” proposals for pursuing new avenues towards a cross-border human resource strategy.
Conference: European International Business Academy 27th Annual Meeting, 13-15 December 2001, Paris
Keywords: M12; 330; IHRM; Internationales Personalmanagement; Personalentwicklung; Management